2016
DOI: 10.1186/s12861-016-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive organ regeneration in Macrostomum lignano

Abstract: BackgroundFlatworms possess pluripotent stem cells that can give rise to all cell types, which allows them to restore lost body parts after injury or amputation. This makes flatworms excellent model systems for studying regeneration. In this study, we present the adhesive organs of a marine flatworm as a simple model system for organ regeneration. Macrostomum lignano has approximately 130 adhesive organs at the ventral side of its tail plate. One adhesive organ consists of three interacting cells: one adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 56 publications
3
55
0
Order By: Relevance
“…Non-covalent cross-linking of polysaccharide chains by carbohydrate-binding proteins had been proposed to support the adhesive proteins secreted by terrestrial gastropod (Pawlicki et al 2004). Lectin staining and proteins with lectin binding domains have been reported in the adhesive secretions of sea stars, sea urchins, frogs, flatworms, and velvet worms (Fleming et al 2009; Hennebert et al 2010; Graham et al 2013; Toubarro et al 2016; Lengerer et al 2016). An investigation using lectins to study sea stars adhesive (Hennebert et al 2010) showed that some glycans, such as galactose, N-acetylglucosamine, fucose and sialic acid residues were linked to the sea star footprint proteins and could provide both cohesive and adhesive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Non-covalent cross-linking of polysaccharide chains by carbohydrate-binding proteins had been proposed to support the adhesive proteins secreted by terrestrial gastropod (Pawlicki et al 2004). Lectin staining and proteins with lectin binding domains have been reported in the adhesive secretions of sea stars, sea urchins, frogs, flatworms, and velvet worms (Fleming et al 2009; Hennebert et al 2010; Graham et al 2013; Toubarro et al 2016; Lengerer et al 2016). An investigation using lectins to study sea stars adhesive (Hennebert et al 2010) showed that some glycans, such as galactose, N-acetylglucosamine, fucose and sialic acid residues were linked to the sea star footprint proteins and could provide both cohesive and adhesive properties.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that the filaments are required to bear the tension forces during attachment (Tyler, 1976). In the free-living marine flatworm M. lignano, anchor-cell-specific intermediate filaments have been identified (Lengerer et al, 2014(Lengerer et al, , 2016. Upon knockdown of these intermediate filaments, the morphology of the anchor cells and their modified microvilli was severely impaired and the animals failed to efficiently attach themselves to the substrate (Lengerer et al, 2014).…”
Section: The Role Of Anchor Cellsmentioning
confidence: 99%
“…Carbohydrates are commonly detected in temporary adhesive glands, but their role in the adhesive process is currently unknown. In the flatworms Schmidtea mediterranea (Zayas et al, 2010) and M. lignano (Lengerer et al, 2016), in the sea star A. rubens (Hennebert et al, 2011), and in the cephalopods Idiosepius spp. (von Byern et al, 2008) and E. scolopes (von Byern et al, 2017), lectin (see Glossary) labelling has been used to characterise carbohydrates and indicated the presence of various sugar moieties within the secretory gland cells (Table S2).…”
Section: Carbohydrate Composition Of the Adhesivementioning
confidence: 99%
See 1 more Smart Citation
“…The free‐living flatworm Macrostomum lignano Ladurner, SchĂ€rer, Salvenmoser, Rieger 2005 (Rhabditophora, Macrostomorpha) has emerged as a model for a broad range of research topics (Ladurner, SchĂ€rer, Salvenmoser, & Rieger, ), including the biology of aging (Mouton, Grudniewska, Glazenburg, Guryev, & Berezikov, ; Mouton et al, ), bioadhesion (Lengerer, Hennebert, Flammang, Salvenmoser, & Ladurner, ; Lengerer et al, ; Wunderer et al, ), regeneration (Egger, Ladurner, Nimeth, Gschwentner, & Rieger, ; Lengerer et al, ), stem cell biology (Grudniewska et al, ; Ladurner et al, ), and sexual selection (Marie‐Orleach, Janicke, Vizoso, David, & SchĂ€rer, ; SchĂ€rer, Littlewood, Waeschenbach, Yoshida, & Vizoso, ; Sekii et al, ). This research has led to the establishment of many resources and tools that are crucial for a modern genetic and genomic model, including in situ hybridization (Pfister et al, ), RNA interference (Kuales et al, ; Sekii et al, ), gene expression (Arbore et al, ; Grudniewska et al, ; Lengerer et al, ), genome and transcriptome assemblies (Wasik et al, ; Wudarski et al, ), transgenesis (Marie‐Orleach, Janicke, Vizoso, Eichmann, & SchĂ€rer, ; Wudarski et al, ), and a clarification of the phylogenetic context (Janssen et al, ; SchĂ€rer et al, ).…”
Section: Introductionmentioning
confidence: 99%